Construction of a high quality database of solar irradiance data for Évora, Portugal. - Wagner, Frank (2010)
The Geophysics Center of Évora performed measurements of solar irradiance at five stations in and around Évora, Portugal. However, as it is normal in such measure-ments, there are data problems that need to be looked up: data gaps, incorrect time, missing re-calibrations, outliers among others. This article deals with the detection of errors in the time series of the individual stations and subsequently how the data of the five stations can be combined to remove errors and to fill data gaps in order to construct a high quality data suitable for renewable energy and especially photovoltaic system applications in the region of Évora. The final irradiance data covers the time period between 2000 and 2009. Hence inter-annual variations can be investigated and taken into account for PV applications, namely in the sizing of the systems.